LATVIAN WRITER AS A PUBLISHER OF HIS OWN WORKS: EDUARDS FREIMANIS’ (1921–2005) CASE - Dreimane, Jana (Knygotyra, 2016)
Authors’ editions in the Latvian book publishing appear in the first half of the 19th century. Self-publishing flourished particularly during the Republic of Latvia (1918–1940). Unfortunately, in the years of the Soviet occupation (1940–1941; 1944–1990) it was forbidden. The tradition could continue only in exile, chosen by many Latvians at the end of World War II. Authors’ self-publishing activity in Latvia began anew after regaining national independence in 1990. So far, the topics related to authors’ editions have not been systematically studied in Latvia. This research is aimed to evaluate the strategies for self-publishing and distribution of works by Eduards Freimanis. He was the first exile writer who published his own works in Latvia after the renewal of independence. The paper describes not only the most important challenges, but also the attitude of contemporaries, colleagues and relatives towards the activities of the writer.
Keywords: book publishing in Latvia; Latvian exile literature; publishing in exile; self-publishing; authors’ editions; book editors; small presses; book trade; Latvian literary criticism; Latvians in Canada